At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Alright, let's solve the given problems step by step.
### Part (a)
We start with the equation:
[tex]\[ 5^8 \div 5^x = 5^2 \][/tex]
Using the properties of exponents, particularly the law of exponents that states:
[tex]\[ \frac{a^m}{a^n} = a^{m-n} \][/tex]
We can rewrite the left-hand side of the equation:
[tex]\[ 5^{8-x} = 5^2 \][/tex]
Since the bases on both sides of the equation are the same, we can set the exponents equal to each other:
[tex]\[ 8 - x = 2 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ 8 - x = 2 \][/tex]
[tex]\[ x = 8 - 2 \][/tex]
[tex]\[ x = 6 \][/tex]
So, the value of [tex]\( x \)[/tex] is:
[tex]\[ x = 6 \][/tex]
### Part (b)
We need to simplify the expression:
[tex]\[ \left( x^5 \right)^3 \][/tex]
Using the law of exponents that states:
[tex]\[ (a^m)^n = a^{m \cdot n} \][/tex]
We can simplify the expression:
[tex]\[ \left( x^5 \right)^3 = x^{5 \cdot 3} = x^{15} \][/tex]
So, the simplified expression is:
[tex]\[ x^{15} \][/tex]
### Summary
(a) The value of [tex]\( x \)[/tex] is [tex]\( 6 \)[/tex].
(b) The simplified form of [tex]\( \left( x^5 \right)^3 \)[/tex] is [tex]\( x^{15} \)[/tex].
### Part (a)
We start with the equation:
[tex]\[ 5^8 \div 5^x = 5^2 \][/tex]
Using the properties of exponents, particularly the law of exponents that states:
[tex]\[ \frac{a^m}{a^n} = a^{m-n} \][/tex]
We can rewrite the left-hand side of the equation:
[tex]\[ 5^{8-x} = 5^2 \][/tex]
Since the bases on both sides of the equation are the same, we can set the exponents equal to each other:
[tex]\[ 8 - x = 2 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ 8 - x = 2 \][/tex]
[tex]\[ x = 8 - 2 \][/tex]
[tex]\[ x = 6 \][/tex]
So, the value of [tex]\( x \)[/tex] is:
[tex]\[ x = 6 \][/tex]
### Part (b)
We need to simplify the expression:
[tex]\[ \left( x^5 \right)^3 \][/tex]
Using the law of exponents that states:
[tex]\[ (a^m)^n = a^{m \cdot n} \][/tex]
We can simplify the expression:
[tex]\[ \left( x^5 \right)^3 = x^{5 \cdot 3} = x^{15} \][/tex]
So, the simplified expression is:
[tex]\[ x^{15} \][/tex]
### Summary
(a) The value of [tex]\( x \)[/tex] is [tex]\( 6 \)[/tex].
(b) The simplified form of [tex]\( \left( x^5 \right)^3 \)[/tex] is [tex]\( x^{15} \)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.